Housing affordability in the state of Johor - Mohamed Osman, Mariana; Ramlee, Muhammad Adib; Samsudin, Nasriah; Rabe, Noor Suzilawati; Abdullah, Muhammad Faris; Khalid, Najihan (Malaysian Institute of Planners, 2017)
The Malaysian property market has been facing significant changes in terms of housing price since a decade ago and these changes are different between states.The changes in housing prices are being supported by the economic theories of demand and supply as well as the regional economic and demographic factors such as income level, housing supply stock, speculative buying and population changes. This paper provides an overview of the affordable housing policy and elaborates on the housing affordability index for the districts in the State of Johor. Using datasets for year 2012 and 2014 in order to determine the median multiple of price-income ratio, this paper found that housing in all the districts were generally unaffordable. Some districts recorded HAI of severely unaffordable, while others in the seriously and moderately unaffordable index categories.